Strengthening Local Economy through Tourism Village: Case Study in Dukuh Dalem, Sleman Regency - Ali Roziqin; Adejaya MS; Khadir Ali (Indonesian Association for Public Administration (IAPA), 2018)
Tourism destination “blue lagoon” contained in dukuh dalem, widodomartani village, District of Ngemplak, Sleman Regency was not many people who know. But, since of 2014, starting from one of student, who updates photos from the river. Then it is be viral (popular) and tourist attraction. The research uses descriptive qualitative methods which data was collected from indepth interview, observation, and literature study. The result is inisiator role can driven to several stakeholders to create tourism village based on-water resources. In addition, management of turism village be supported by any stakeholders such as, governments, community, and private sector. Another effect is tourist attraction